Administrative Burden Scale – Development and Psychometric Properties: Administrative Burden Scale – Development and Psychometric Properties - Shabana Noureen; Shamaila Asad (Research Journal of Psychology, 2024)
The research on administrative burden is highly important as it provides a tool to measure and address administrative burdens in academic settings, contributing to improved work efficiency and job satisfaction. Teaching and research responsibilities, along with administrative burdens such as paperwork and institutional requirements, place significant demands on assistant professors in universities. The purpose of the study was to develop the administrative burden scale (ABS) for assistant professors in the English language. The study was conducted in different steps. Initially, a construct was conceptualized, and then an item pool of 55 items was generated for the administrative burden. After that committee approach was involved to determine face and content validity through the item content validity index (I-CVI) based on 7 experts. Later on, pilot testing was conducted on 30 assistant professors, selected through a purposive sampling technique. Lastly, exploratory factor analysis was performed on a sample of 200 assistant professors. The ABS consisted of 24 items divided into 4 subscales - documentation & paperwork, meetings & committees, students support & communication, and research & publication. Four factors account for 69.23% variance in the dataset, which play a substantial role in explaining the observed variability, providing valuable information about the underlying structure of the construct. All the factors had an alpha reliability of more than 0.70, which supports the notion of internal consistency. The study was able to create a valid scale which defines areas that assistant professors consider to be most administratively demanding. It is a useful tool in understanding the burdens that these employees experience. Its use can help design policies and interventions that alleviate administrative burden thus enhancing faculty health and productivity in teaching and research.